Digital Entrepreneurship in the Last Decade: A Systematic Review - Chimezie Amadi; Umaru Mustapha Zubairu; Olalekan Busra Sakariyan; Isah Imam Paiko (Fakultas Ekonomi, Universitas Negeri Jakarta, 2021)
The objective of this paper is to investigate the effects ICT has on the sustainability of Digital Entrepreneurship in Nigeria. Furthermore, this paper seeks to determine if the utilization of ICT can forecast the rate of start-ups in the Digital Entrepreneurship sector and interrogate the characteristics and inter-relationships inherent in Digital Entrepreneurship. To achieve this objective, a systematic literature review using the Systematic Quantitative Assessment Technique (SQAT) was the methodology used to review 45 DE articles published over the last decade (2012 – 2021). To provide a thorough, impartial amalgam of the reviewed articles, this paper analysed the time distribution, geographic distribution, types and data collection methods of the 45 DE articles. The review revealed that existing research has been both empirical and conceptual in equal measure with only one instance in mixed mode. The parity suggests that future researchers should endeavour to conduct more conceptual research to underpin the envisaged accelerated growth of DE.